BLOOD PRESSURE CONTROL AMONG AN ELDERLY NORTHERN-ITALIAN POPULATION, EFFECT OF BETA-ADDUCIN POLYMORPHISMS. A CROSS-SECTIONAL STUDY. (June 2022) - Betti, Paolo; Lanzani, Chiara; Citterio, Lorena; Zagato, Laura; Messaggio, Elisabetta; Brioni, Elena; Magnaghi, Cristiano; Simonini, Marco; Querini, Patrizia Rovere; Manfredi, Angelo; Manunta, Paolo
Abstract : Objective: Evaluate role of nvironmental and genetic factors on Blood Pressure (BP) control among an Italian elderly population. Design and method: Cross-sectional study on 1250 elderly subjects of north Italy aged over 65y, recruited in recreative centers. BP was measured with an automated device (Omron) and the average of 2nd and 3rd measure was recorded. According to ESC-ESH-2018 guidelines we defined suboptimal BP control for patients presenting with systolic BP>140 or diastolic BP>80 mmHg. Anthropometric measurements were taken, blood and urines samples for biochemical and targeted genetic analysis were acquired. Genotyping was performed by OpenArray system. All participants signed informed consent. The protocol was approved by the Ethical Committee. Results: 746 subjects (59.9%) were on antihypertensive therapy. 385 (51.6%) had a systolic BP over 140 mmHg, and 419 (56.2%) had a diastolic BP over 80 mmHg, thus classified as on suboptimal BP control. Among those, 153 (20.4%) presented SBP> 160 or DBP > 100 (stage 2 hypertension) despite treatment. 28.6% were on optimal BP control. Factors associated with poor BP control on univariate analysis showed gender (p = 0.002), higher waist circonference (p = 0.014), high visceral fact index (p < 0.01) and minor number of total medications (p < 0.01). Age, eGFR, and urine albumin/creatinine ratio were non significantly different between the two groups. Inferential tree analysis showed that urine sodium is relevant on BP level in 'younger' and untreated subjects (p < 0.001). Among genetic variants, rs4984 T allele in beta-adducin gene (ADD2) was associated with poor BP control (17.3% vs 11.4%; p = 0.016). Similarly, T allele in the overall elderly subjects showed a high frequency compared to general population (EUR - 1000 Genome Project) (16% vs 12.5%; p = 0.023). Conclusions: Gender, visceral fat and therapies are associated with poor BP control, suggesting the relevant role of clinical management. Surprisingly, even in this elderly population, a genetic factor already associated with salt-sensitive hypertension and response to anti-hypertensive therapy as ADD2 was found related to poor BP control. Most of of elderly patients treated for hypertension have suboptimal control of BP. Moreover, genetic factors besides environmental factors, seem to play a role in BP control even in elderly.